THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF STUDENTS' VALUEOLOGICAL SKILLS BASED ON INTEGRATIVE TEACHING OF PHILOSOPHY (World Bulletin of Education and Learning, 2026)
This article examines the theoretical and methodological foundations for developing students’ valeological skills through the integrative teaching of philosophy. It is argued that contemporary global challenges necessitate a shift from fragmented education toward holistic, interdisciplinary models aimed at fostering a culture of health, stress resilience, and personal responsibility. The role of philosophy as a worldview-based foundation for the formation of health consciousness is substantiated. The study explores the integration of philosophy, valeology, and psychology within higher education. Particular attention is given to modern pedagogical technologies, including vitagenic learning and the development of sanogenic thinking, which facilitate the transformation of theoretical knowledge into sustainable health-preserving behaviors. The results of the experimental implementation of the “Health Trajectory School” model confirm the effectiveness of the integrative approach in developing students’ valeological culture.
Keywords: Integrative learning, philosophy of education, valeology, valeological competence, sanogenic thinking, vitagenic learning, health culture, stress resilience, pedagogical technologies, interdisciplinary approach.